Toxicity Test of Red-Shoot Leaves (Syzygium myrtifolium Walp.) Extract as Biolarvicide on Filariasis Vector Mortality - Supriatno Supriatno; Riska Riska; Hafnati Rahmatan; Yaumil Istiqlal M. Nur; Fitra Asma Ulhusna (Postgraduate, University of Mataram, 2024)
The Control of Culex sp. using synthetic larvicides is harmful to the environment and human health. Biolarvicide from red shoot leaves (Syzygium myrtifolium) is a safe alternative for the environment and human health. This study aims to determine the effect of Syzygium myrtifolium leaves extract with ethanol solvent and water solvent on larval mortality and the LC50 values of these extracts. ANOVA test results (α = 0.05) on the mortality of Culex sp. larvae exposed to the ethanol extract and aqueous extract of S. myrtifolium leaves consecutively showed F-calculated (287)>F-tabulated (3,11) and F-calculated (153)>F-tabulated (3, 11). The treatment of S. myrtifolium leaves extract with ethanol and water solvents had a significant effect on the mortality of Culex sp. larvae. The LC50 value of the ethanol extract and the aqueous extract of S. myrtifolium leaves are 1659 ppm and was 2053.7 ppm. It can be concluded that S. myrtifolium leaves extracts with ethanol solvent and water solvent have an effect on the mortality of Culex sp. larvae, but are not yet effective as biolarvicide